Association of XRCC3 Thr241Met polymorphism and leukemia risk: evidence from a meta-analysis. Issue 9 (September 2014) - Yan, Yulan; Liang, Hongjie; Li, Taijie; Guo, Shihui; Li, Meng; Qin, Xue; Li, Shan
Abstract The relationship between the X-ray repair cross-complementing group 3 (XRCC3) Thr241Met (rs861539) polymorphism and the risk of leukemia remains inclusive or controversial. For a better understanding of the effect of XRCC3 Thr241Met (rs861539) polymorphism on leukemia risk, we performed a meta-analysis. All eligible studies were identified through a search of PubMed, Excerpta Medica Database (Embase) and the Chinese Biomedical Literature Database (CBM) up to August 2013. The association between the XRCC3 Thr241Met (rs861539) polymorphism and leukemia risk was analyzed by means of odds ratios (ORs) and 95% confidence intervals (CI). Ultimately, seven studies with 1070 cases and 1850 controls were included in the meta-analysis. There was no association between Thr241Met polymorphism and leukemia risk in any of the five models in the overall populations (T vs. C: OR = 1.43, 95% CI = 0.95–2.13, p = 0.086; TT vs. CC: OR = 1.71, 95% CI = 0.88–3.33, p = 0.112; TC vs. CC: OR = 1.35, 95% CI = 0.96–1.91, p = 0.089; TT vs. TC/CC: OR = 1.59, 95% CI = 0.87–2.89, p = 0.132; TT/TC vs. CC: OR = 1.37, 95% CI = 0.98–1.94, p = 0.070). In subgroup analysis according to ethnicity, a significant association was found between XRCC3 Thr241Met (rs861539) polymorphism and leukemia risk in Asian but not in Caucasian or mixed populations. In conclusion, the results suggest no association between XRCC3 Thr241Met (rs861539) polymorphism and leukemia risk in the overall populations but a significant association between XRCC3 Thr241Met (rs861539) polymorphism and leukemia risk in the Asian population. Considering the limited sample size and ethnicities included in the meta-analysis, further large-scale, well-designed studies are needed to confirm our results.